ANALISIS KEPUASAN TAMU: Kualitas Pelayanan Dan Fasilitas Pada D’Senopati Malioboro Grand Hotel Yogyakarta - Nurlaili, Septi; Wijoyo, Tuwuh Adhistyo (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
This study intends to look at how the D'Senopati Malioboro Grand Hotel Yogyakarta's amenities and level of service affect visitors' happiness. Using a sample of 92 respondents, multiple linear regression analysis was used in the research methodology. Guest satisfaction is positively and significantly impacted by the quality of the facilities and services, according to the analysis's findings. It's interesting to note that the degree of client pleasure is more influenced by service quality than by facilities. This discovery could lead to talks about investments and resource allocation in the hotel sector, with a focus on raising service quality. The investigation also emphasizes the significance of favorable reactions to facilities and the difficulties associated with correct information provided by staff members. The research's practical implications offer a strong basis for hotel management to develop a comprehensive plan aimed at maximizing visitor satisfaction through improved amenities and service standards.